Using Overture to enhance students’ aural musical skills and motivation in learning - Madhawa Nair, Subadrah; You, Jiaojing; N Krishnasamy, Hariharan; Kaur Saminder Singh, Gurdip; Siddique, Muhammad (Edelweiss Applied Science and Technology, 2024)
Aural musical skills are a compulsory course for music students, but studies show that students are weak in this area due to unattractive and ineffective teaching methods. This study investigated the effects of Overture on enhancing the aural musical skills of students in China. In addition the study also investigated whether the utilization of Overture can enhance students' motivation to learn aural musical skills. This quasi-experimental study only used quantitative data. The researchers chose 70 first-year Chinese music students as an intact group sample, from Hunan City University in China, The experimental group was taught using the Overture method, while the control group was taught using the conventional method. The intervention was for eight weeks. The researchers used pre-test, post-test, and questionnaires on learning motivation as instruments to collect the data. The data was analyzed using the SPSS program for Windows, version 25 (ANCOVA test). The results indicated that the experimental group performed significantly better and outperformed the control group in their overall scores in aural musical skills, melodic intervals, rhythmic patterns, monophonic music, and two-voice music, The experimental group also showed significantly higher motivation than the control group. In terms of pedagogical implications, this study suggests that music lecturers need to consider using Overture as an alternative method to improve aural musical skills among students and they have to be trained on how to utilize Overture for teaching music.